EKONOMI ISLAM DAN PEMBERDAYAAN EKONOMI RAKYAT - ANWAR ABBAS (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Islam has made an effort to balance between policy-oriented intervention and non-policyoriented intervention on economy. As a religion, Islam does not oppose the market’s view of economy (liberal economics) nor the state’s control over the economy. Rather, Islam tries to make the balance equally according to the level and the measurement between the two. In principle, Islam recognizes the concept of altruism that gives precedence to the willingness to work cooperatively. In Indonesia, this principle lies in the existence of cooperatives (koperasi). This article argues that the system of cooperatives has its root in Islamic principles called atta’âwun, meaning cooperation and togertherness. By taking Koperasi Pondok Pesantren Sidogiri Pasuran as its case study, this article found that koperasi managed to enhance the level of economic betterment of its members.